Robotic versus Open Thyroidectomy for Differentiated Thyroid Cancer: An Evidence-Based Review - Shirley Yuk Wah Liu; Enders Kwok Wai Ng (International Journal of Endocrinology)
While open thyroidectomy (OT) is advocated as the gold standard treatment for differentiated thyroid cancer, the contemporary use of robotic thyroidectomy (RT) is often controversial. Although RT combines the unique benefits of the surgical robot and remote access thyroidectomy, its applicability on cancer patients is challenged by the questionable oncological benefits and safety. This review aims to analyze the current literature evidence in comparing RT to OT on thyroid cancers for their perioperative and oncological outcomes. To date, no randomized controlled trial is available in comparing RT to OT. All published studies are nonrandomized or retrospective comparisons. Current data suggests that RT compares less favorably than OT for longer operative time, higher cost, and possibly inferior oncological control with lower number of central lymph nodes retrieved. In terms of morbidity, quality of life outcomes, and short-term recurrence rates, RT and OT are comparable. While conventional OT continues to be appropriate for most thyroid cancers, RT should better be continued by expert surgeons on selected patients who have low-risk thyroid cancers and have high expectations on cosmetic outcomes. Future research should embark on prospective randomized studies for unbiased comparisons. Long-term follow-up studies are also needed to evaluate outcomes on recurrence and survival.